The Influence of Green Accounting Implementation and Information and Communication Technology on the Sustainability of Micro and Small Enterprises in Mining and Non-Mining Areas - Putri, Amelia Hamdani; Mile, Yuldi; Muliati, Muliati; Utari, Adiani Purwa (Jurnal Ekonomi dan Bisnis Digital, 2025)
The instability of the global environment has led various parties to pay special attention to social responsibility and the sustainability of micro and small enterprises (MSEs) to ensure their continued growth. This study aims to analyze the influence of green accounting implementation and information and communication technology (ICT) on the sustainability of MSEs in mining and non-mining areas. The study adopts a quantitative approach using a survey of MSEs in Palu City, analyzed with multiple regression methods. The results show that the implementation of green accounting and ICT impacts the sustainability of MSEs. Moderated by business location, it was found that green accounting implementation positively affects the sustainability of MSEs in mining areas, whereas ICT has no significant influence on the sustainability of MSEs in these areas. These findings underline the importance of providing new insights into MSE sustainability strategies that address current environmental challenges, particularly for MSEs in mining areas. A proper understanding of the role of the business environment can serve as a crucial strategy for fostering more sustainable MSE development.